PENERAPAN FILM INDUCED TOURISM DALAM SERIAL NETFLIX â€œTWOGETHER: EPISODE LETâ€™S FIND OUT WHOSE FAN LIVING HERE?â€ DI YOGYAKARTA - Adityaji, Rizki; Widyawati, Christy; Rorimpandey, Pascha Argenia (Jurnal Pariwisata Pesona, 2021)
This study discusses the implication of Â Film Induced Tourism on Netflix series Twogether , episode â€œLetâ€™s Find Out Whose Fan Living Here?â€Yogyakarta, toward the society and tourism promotion. There is a phenomenon, in which many people have curiosity after watching the series. They want to visit the locations used for filming. Many online platforms have responded positively to the Netflix series Twogether. This study aims to determine the impact of implementing Film Induced Tourism on local community, especially the impact of the Netflix series Twogether and to determine the effect of the Netflix series Twogether that can make people want to visit the location. This research was conducted using a qualitative method â€“ content analysis in which researchers collected data through an online platform and also by conducting interviews with related informan who are directly imfluenced by the film and directly involved in making the Netflix series Twogether. Based on the results of data analysis, Film Induced Tourism received a positive response from the community, and also also influence tourist destinations promotion.